Mapping rural-urban differences in state expenditures with geospatial methods – explorative spatial data analysis from Finland - Lehtonen, Olli; Makkonen, Teemu; Vihinen, Hilkka; Hirvonen, Timo; Rautiainen, Simo; Voutilainen, Olli (Pergamon Press, 2025)
State expenditures are pivotal to the economies of industrialized nations, serving redistributive, allocative, and regulatory functions that mitigate income inequality, provide public goods, and promote sustainable development. Despite their significance, the geographical distribution of these expenditures has been under-researched, primarily due to data limitations. Existing studies have often focused on specific regions or categories of expenditure. This study aims to offer a comprehensive analysis of state expenditure allocation across rural and urban municipalities in Finland. Utilizing a unique dataset from 2018 to 2021, it employs explorative spatial data analysis to uncover spatial dependencies and inequalities. The findings provide valuable insights into the spatial distribution of state expenditures, emphasizing the critical role of geographical allocation decisions in promoting spatial equity and regional development. The study highlights the necessity for a holistic understanding of state expenditure distribution to inform policy decisions that foster favourable development conditions across various municipalities.
Keywords: state expenditures; municipalities; rural-urban; spatial formations; Finland; exploratory spatial data analysis